Penyambutan Bulan-Bulan Khusus (Bulan Suci Ramadhan dan Isra Mi’raj) Dengan Tradisi Maapam di Kampung Padang Panjang Nagari Talu, Pasaman Barat - Yurisa Mailani (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2023)
This research is motivated by the traditions carried out by the people in West Pasaman in welcoming special months, such as welcoming the holy month of Ramadan and commemorating the Isra Mi'raj day which is still carried out today, namely by carrying out the maapam tradition. the purpose of this research is to find out about the maapam tradition that has been carried out by the Nagari Talu community, especially in the Padang Panjang village. This study uses a qualitative method with a descriptive approach. Source of data comes from primary and secondary data. Data collection techniques with observation, interviews, and documentation. Data analysis techniques with data reduction, data display, and conclusions. The results of this study show that if the maapam tradition is still running today, with the maapam activities a friendship can be established because it is done together, and presents laughter and cohesiveness.